Revision of the Neotropical genus Malacophagomyia (Diptera: Sarcophagidae) with description of a new species - Mulieri, Pablo Ricardo (2013)
The small Neotropical genus Malacophagomyia Lopes is revised. Two previously recorded species from tropical South America are redescribed: M. filamenta (Dodge) and M. kesselringi Kano & Lopes. One new species is described, M. rivadavia sp. nov., from temperate southern South America. The structures of the male genitalia of the species of this genus are compared, and some female genitalic structures of M. filamenta are reinterpreted. Diagnostic characters to recognize the three species are given. Additionally, a key to described species of Malacophagomyia is presented.